Coronary bifurcation lesions: Present status and future perspectives. (6th May 2015) - Leesar, Massoud A.; Hakeem, Abdul; Azarnoush, Kasra; Thuesen, Leif
Abstract: Coronary bifurcation lesions (CBLs) are challenging and associated with a higher rate of adverse events than non-bifurcation lesions. In the era of drug-eluting stents, 2 primary interventional strategies for treating CBL include the complex strategy the main vessel (MV) and side-branch (SB) stenting, and the simple strategy MV stenting combined with provisional SB stenting. The meta-analysis of the simple vs. complex strategies demonstrated an increased incidence of myocardial infarction in the complex strategy. Likewise, the Tryton dedicated bifurcation stents, as compared with the simple strategy, increased the rate of myocardial infarction. In contrast, the Nordic–Baltic Bifurcation Study IV demonstrated that event rates were not significantly different comparing the simple vs. complex strategies in true bifurcation lesions involving a large SB. Fractional flow reserve (FFR) has emerged as a powerful catheter based tool for the functional assessment of a stenosis, but the role of FFR on the long-term outcomes of patients with CBL has not been studied. Given the recent evidence that Tryton stents (a dedicated bifurcation stent) increased event rates, and the lack of benefit from using 2-stent techniques (the Nordic Baltic Bifurcation Study IV) in true CBL, assessing the FFR of the SB seems now of outmost importance, but randomized data are lacking. An intravascular study showed that kissing balloon inflation (KBI) significantly reduced SB stenosis, restored stent lumen at the carina, and expanded stent in the proximal segment. However, a recent randomized study showed no significant benefit of routine KBI. This review highlights current concepts and future perspectives in patients with CBL. Highlights: The simple strategy with provisional side-branch stenting is now a preferred strategy. Randomized trials are warranted to investigate the role of FFR assessment of SB stenoses. Randomized trials are needed to investigate the impact of kissing balloon inflation on outcomes.